2020
DOI: 10.1128/jcm.00557-20
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Performance of SARS-CoV-2 Detection Assays Using Seven Different Primer-Probe Sets and One Assay Kit

Abstract: 25Nearly 400,000 people worldwide are known to have been infected with SARS-CoV-2 beginning 26 in December 2019. The virus has now spread to over 168 countries including the United States, where 27 the first cluster of cases was observed in the Seattle metropolitan area in Washington. Given the rapid 28 increase in the number of cases in many localities, the availability of accurate, high-throughput SARS-29CoV-2 testing is vital to efforts to manage the current public health crisis. In the course of optimizing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
271
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 428 publications
(294 citation statements)
references
References 4 publications
13
271
0
3
Order By: Relevance
“…Participants who had a positive nasopharyngeal (NP) swab as part of routine clinical care were recruited for enrollment into the Hospitalized and Ambulatory Adults with Respiratory Viral Infections (HAARVI) study at the University of Washington. These clinical samples were established to be COVID-19-positive via testing at the University of Washington’s Virology lab ( 3 ). Paired conventional and dry mid-nasal swabs were then self-collected via Seattle Flu Study (SFS) home self-swab kits delivered to participants’ homes within 1-2 days after they had tested positive, and returned via delivery service at ambient temperature ( 4, 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Participants who had a positive nasopharyngeal (NP) swab as part of routine clinical care were recruited for enrollment into the Hospitalized and Ambulatory Adults with Respiratory Viral Infections (HAARVI) study at the University of Washington. These clinical samples were established to be COVID-19-positive via testing at the University of Washington’s Virology lab ( 3 ). Paired conventional and dry mid-nasal swabs were then self-collected via Seattle Flu Study (SFS) home self-swab kits delivered to participants’ homes within 1-2 days after they had tested positive, and returned via delivery service at ambient temperature ( 4, 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, in‐house clinical validations upon implementation of novel RT‐PCR kits need to be conducted. Thus far, several studies have been devoted to this topic, but the majority of them assessed these products using different kits 9‐12 . Only a study by Shen et al evaluated the same Sansure PCR kit that we evaluated, 10 and they found sensitivity, specificity, PPV, NPV, and kappa values of 95.00%, 87.50%, 95.00%, 87.50%, and 0.825, respectively, for the Sansure PCR kit (Lot No.…”
Section: Discussionmentioning
confidence: 99%
“…The study found high specificity among all primer sets and variable sensitivity, with the CDC N2 and the Germany E-gene sets being more sensitive than others. 11 Another study (in preprint) examined the sensitivity and efficiency of four 12 Other studies have also compared the US CDC N1 and N2 against commercial test kits, reporting similar specificity with variable sensitivity. 13,14 To accelerate testing capacity, the US Food and Drug Administration (FDA) released updated guidance on February 29, 2020, opening up the production of diagnostic kits to state laboratories, laboratories certified under Clinical Laboratory Improvement Amendments (CLIA), and commercial diagnostic developers.…”
mentioning
confidence: 99%